Through‐wall detection and imaging of a vibrating target using synthetic aperture radar. Issue 15 (1st July 2017) - Corbett, B.; Andre, D.; Finnis, M.
Abstract : The development of a through‐wall synthetic aperture radar (SAR) simulator, which is being used to investigate the SAR artefacts originating from vibrating target's, known as paired echoes is explained. The simulation and experimental results both show that paired echoes can be detected and imaged through a wall, with a noticeable reduction in intensity, resulting in the number of visible echoes to be reduced in brightness and appear shifted in location in a through‐wall SAR image.